Serum erythropoietin levels in patients wıth severe anemıa secondary to inflamatorybowel dısease and the use of recombinant human erytropoietin in patıents with anemia refractory to treatment - Levent DEMİRTÜRK and Saadeddin HÜLAGÜ and Mustafa YAYLACI and A. Kemal GÜRBÜZ and Mehmet ALTIN and Melih ÖZEL and Ali ÖZCAN (Turkish Journal of Gastroenterology, 2020)
-